2017
DOI: 10.1007/s10741-017-9613-8
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in cardiac transplantation: an evolving model

Abstract: It is currently estimated that 5.7 million Americans live with heart failure. Of these, less than 3000 will receive a heart transplant this year, according to the US Department of Health and Human Services Organ Procurement and Transplantation Network. With successful transplantation can come significant emotional and physical symptoms that are not always addressed. Although palliative care is an interdisciplinary subspecialty designed to alleviate multiple domains of suffering in serious illness, many mistake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
11
0
3
Order By: Relevance
“…Aging, co‐morbid conditions, end‐organ damage, cognitive impairment, frailty and limited social support complicate heart failure management, and palliative care should address each of these components. End‐of‐life decision making is even more challenging for patients with advanced heart failure when heart transplantation or long‐term MCS have failed . The PAL‐HF (Palliative Care in Heart Failure) trial, a single‐centre study of 150 patients, showed that interdisciplinary palliative care intervention in advanced heart failure patients resulted in greater benefits in quality of life, anxiety, depression and spiritual wellbeing compared with usual care alone .…”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%
See 3 more Smart Citations
“…Aging, co‐morbid conditions, end‐organ damage, cognitive impairment, frailty and limited social support complicate heart failure management, and palliative care should address each of these components. End‐of‐life decision making is even more challenging for patients with advanced heart failure when heart transplantation or long‐term MCS have failed . The PAL‐HF (Palliative Care in Heart Failure) trial, a single‐centre study of 150 patients, showed that interdisciplinary palliative care intervention in advanced heart failure patients resulted in greater benefits in quality of life, anxiety, depression and spiritual wellbeing compared with usual care alone .…”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%
“…A comprehensive end‐of life plan of care for each patient should be available. This plan of care should be defined before MCS implantation or heart transplantation and revisited during the course of care …”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…liver) describes their limited involvement in advance care planning (ACP) [6][7][8][9][10] and high burden of unmet palliative care needs. [11][12][13][14][15] Although results are mixed, 10,16 there is some evidence that patients preparing for these other types of solid organ transplant received more intensive patterns of end-of-life care than similar patients who had not been considered for transplant, even when their death was expected. 8 However, systematic differences in the selection process for kidney, as compared with other kinds of solid organ transplant, 17 and the availability of dialysis as an alternative form of organ replacement therapy for people with ESKD may contribute to distinctive patterns of end-of-life care for patients engaged in the kidney transplant process.…”
mentioning
confidence: 99%